Functional Analysis of Narrative Texts in Elementary School Textbook “Fly with English” - Ambar Jati; Manu Somphithak (Nur Science Institute, 2021)
Background: This study is an analysis of narrative texts in Elementary School textbook “Fly with English” based on lexico-grammar and context in the framework of Systemic Functional Linguistics (SFL). This study is also expected to give the pedagogical implication based on the context of teaching and learning process Method: This research uses descriptive qualitative type of study in investigating the problem. In the technique of collecting data, the writer uses observation and documentation. The writer finds 95 clauses in narrative text. In analyzing the data, the writer uses lexico-grammar of SFL framework to answer the first problem. Moreover, the writer refers to context of SFL framework to answer the second problem, and the writer also uses context of teaching and learning to answer the third problem. Result: Based on the result, there are six types of processes in the narrative text, those are: (1) material process (40%), (2) mental process (23,1%), (3) relational process (20%), (4) verbal and behavioral process (7,4%), and (5) existential process (2,1%). The writer also finds fifteen types of the participants, namely actor, goal, senser, phenomenon, sayer, verbiage, carrier, attribute, token, value, receiver, client, recipient, behaver, and existent. Moreover, the writer finds six types of circumstances, that are, location, matter, manner, accompaniment, cause, and extent. Implication: The pedagogical implication of studying Systemic Functional Linguistics (SFL) in narrative text is to give the insight of the teacher about SFL genre pedagogy in teaching and learning process. In functional grammar, teacher can teach the language features in different ways, such as by introducing the terms of processes, participants, and circumstances that contain in the narrative text clauses.